Enchancing Online Consumer Experience Through Artificial Intelligence In CRM: The Mediating Role of Digital HR - Mahadewi, Erlina Puspitaloka; Sanantagraha, Arnastya Iswara (International Journal of Artificial Intelligence Research, 2024)
This study aims to analyze the impact of implementing Artificial Intelligence (AI) in managing Customer Relationship Management (CRM) on online consumer experience, with the role of digital HR as a mediator. The implementation of AI in CRM has become an increasingly popular strategy among companies to improve customer interaction, personalization, and satisfaction. However, its effectiveness depends not only on the technology used, but also on the ability of digital HR to manage and optimize it. The research method used is a quantitative approach with a survey of 200 online consumers who interact with companies that use AI-based CRM. Data were analyzed using a path analysis model to test the direct and indirect relationships between independent variables (AI implementation in CRM), mediator variables (digital HR competencies or roles), and dependent variables (online consumer experience). The results of the study show that the implementation of AI in CRM has a significant positive effect on online consumer experience. In addition, digital HR competency acts as a strong mediator, where high HR quality in managing AI technology strengthens the relationship between AI use and improved consumer experience. These findings indicate that in addition to investing in AI technology, companies need to focus on improving digital HR competency to achieve optimal results. This research provides practical implications for companies in designing more effective customer management strategies by combining AI technology and HR development. In addition, these results also provide insights for academics for further research on the role of digital HR in the era of automation and digitalization.